NAVIGATING TRANSLATION PROBLEMS IN ENGLISH: CHALLENGES AND SOLUTIONS - Qarshiyeva Nafisa Mamarahim qizi, Xudoyorova Ziyoda Husinovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is about an analysis of several problems encountered in translating a work from English and an explanation of each problem. This article provides information about the obvious translation problems.